The geometry of GL(2,q) in translation planes of even order q2 - N. L. Johnson (International Journal of Mathematics and Mathematical Sciences, 1978)
In this article we show the following: Let π be a translation plane of even order q2 that admits GL(2,q) as a collineation group. Then π is either Desarguesian, Hall or Ott-Schaeffer.